On the study of machining characteristics of 2-D nanoscale material - Vijayaraghavan, V. (2015)
An Integrated approach of molecular dynamics (MD) is proposed in this work to model the nano-manufacturing drilling phenomenon of Boron Nitride Nanosheet (BNN) panels. An Integrated approach consists of nano scale modeling using MD simulation and a computational intelligence approach comprising of a general regression neural network, which was specifically designed to formulate the machining force and time models for studying the output features of BNN panel with respect to process temperature, feed and rotational velocity of drill bit. We find that our integrated MD model is able to model the drilling process of BNN panel very well, and the results are in well agreement with the experimental data. The sensitivity and parametric analysis is conducted, which validates the robustness of our proposed model by unveiling hidden dominant input parameters and non-linear relationships of drilling of BNN panel. It was found that the rotation velocity has the highest influence on the machining force and time in drilling of BNN panel.